Main enablers for advanced interference mitigation. Issue 1 (28th August 2012) - Zirwas, Wolfgang; Mennerich, Wolfgang; Khan, Aneeq; Dammann, Armin; Plass, Simon; Fazel, Khaled
ABSTRACT The vision of an interference‐free or interference‐exploiting mobile cellular radio system has attracted lots of research groups. It led to several 3GPP long term evolution coordinated multipoint transmission studies and working items. So far, the results achieved are still far from theoretical performance as expected from network‐wide cooperation. In reality, small to moderate gains will be easily lost in case of realistic channel estimation and feedback assumptions. Therefore, the European Union founded project ARTIST4G had a three‐fold goal: leveraging considerable system level gains in combination with an effective channel estimation and a low rate feedback scheme. One main enabler is the so‐called partial coordinated multipoint plus cover shift concept of overlapping cooperation areas approaching user centric clustering. 'Simple' but powerful is a novel interference floor shaping technique based on cooperation area specific vertical antenna tilting and power allocation. An enhanced scheduling strategy turns signal to interference and noise into spectral efficiency and coverage gains. For overcoming channel state information outdating and simultaneously minimizing feedback overhead, a model‐based channel prediction concept is proposed reporting location instead of channel state information. Copyright © 2012 John Wiley & Sons, Ltd.